Modern Music: The Avant Garde since 1945 - Griffiths, Paul (London Dent, 1981)
A look at music since 1945 focuses on the development of new instrument technology, the theory of serialism, and the use of chance or choice in composition
Keywords: 20th Century (1901-2000); Music history